An archive childhood, memory, and the Cold War - Millei, Zsuzsa; Piattoeva, Nelli; Silova, Iveta (Open Book Publishers, 2024)
"What was it like growing up during the Cold War? What can childhood memories tell us about state socialism and its aftermath? How can these intimate memories complicate history and redefine possible futures? These questions are at the heart of the (An)Archive: Childhood, Memory, and the Cold War. This edited collection stems from a collaboration between academics and artists who came together to collectively remember their own experiences of growing up on both sides of the 'Iron Curtain'. Looking beyond official historical archives, the book gathers memories that have been erased or forgotten, delegitimized or essentialized, or, at best, reinterpreted nostalgically within the dominant frameworks of the East-West divide. And it reassembles and (re)stores these childhood memories in a form of an 'anarchive': a site for merging, mixing, connecting, but also juxtaposing personal experiences, public memory, political rhetoric, places, times, and artifacts. These acts and arts of collective remembering tell about possible futures-and the past's futures-what life during the Cold War might have been but also what it has become. (An)Archive will be of particular interest to scholars in a variety of fields, but particularly to artists, educators, historians, social scientists, and others working with memory methodologies that range from collective biography to oral history, (auto)biography, autoethnography, and archives."--Publisher's website.
"Mnemo ZIN is a composite name for Zsuzsa Millei, Iveta Silova, and Nelli Piattoeva"--Publisher's website
Keywords: Kollektives Gedächtnis; Eiserner Vorhang; Ost-West-Konflikt; Kind